FACTORS INFLUENCING MOBILE BANKING ADOPTION IN IRANIAN CLIENTS - Mousavian, Seyed Javad; Abbasi, Hila (APPS Publications, 2021)
Today, learning to use a mobile phone is an opportunity for financial institutions and banks to take advantage of it in a competitive environment. Therefore, this research aims to study factors affecting the adoption of mobile banking in Iran. For collecting research data, we used a questionnaire. A necessary sample of this research was selected among referred bank customers in Iran. Finally, 309 questions were suitable for this research, and structural equation modeling was used for data analysis. Results showed that, among of 7 hypotheses, five hypotheses were confirmed, and two hypotheses were rejected. In other words, founded relative preference, founded consistency, perceived competence, perceived integrity on theory of mobile banking adoption were confirmed and perceived ease and perceived benevolence on theory of mobile banking adoption were not confirmed. Finally, the final hypothesis, namely, attitudes of mobile banking adoption on behavioral intentions about mobile banking use, was confirmed.